Agricultural development in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Facilitating sustainable agricultural development in Zimbabwe: key factors and necessary incentives 1994 99pp ISBN 3 38935 1274 German Development Institute, Hallerstrasse 3, D- 10587 Berlin, GERMANY